Do Entrepreneurship and Sectoral Outputs Support Sustainable Development: A Literature Review and an Empirical Assessment for Developed Countries - Daly, Saida; Garroud, Chadia (Asian Journal of Economic Modelling, 2022)
The objective of this paper is to explore the relationship between entrepreneurship and sectoral outputs and three dimensions of sustainable development using the FMOLS technique for a panel of 21 developed countries covering the period 2001-2016. Our empirical results reveal that entrepreneurship and sectoral outputs have a significant positive impact on economic growth. They also indicate that entrepreneurship and sectoral outputs could play an essential role in resolving environmental problems. Our findings also show that entrepreneurship and sectoral outputs can support human development. On a global level, we can say that entrepreneurship and sectoral outputs could reinforce sustainable development.